Implementasi 8 Keterampilan Dasar Mengajar dalam Menciptakan Pembelajaran Aktif di TK Lebijaga - Mari Aprinianti Beo; Sklolastika Mude; Maria Cerlina Isa Kajo; Stefania Seku; Elisa Yunita Sada; Nofrianus Talu Popo; Maria Yasinta Fengi (Jurnal Lensa Pendas, 2026)
This research aims to describe the application of eight basic teaching skills performed by teachers in an effort to realize active learning in TK Lebijaga. The research used a qualitative approach with a descriptive design. The subjects of the study were teachers of TK Lebijaga who were directly involved in the implementation of learning in the classroom. Data collection techniques included observation, interviews, and documentation. The research instruments were observation sheets and interview guidelines prepared based on eight basic teaching skills, including the skills of opening and closing lessons, asking questions, explaining, providing reinforcement, varying learning, managing the class, guiding small groups, and teaching individually. The results showed that the teacher had implemented the eight basic teaching skills well and in accordance with the developmental characteristics of early childhood. The application of these skills had a positive impact on children's activeness in learning, which was indicated by increased enthusiasm, courage to participate, and children's physical, mental, and emotional involvement during learning activities. Although constraints were still found in the form of differences in children's abilities and attention levels, the teacher tried to adjust learning strategies so that all children could participate optimally. Thus, the application of eight basic teaching skills has an important role in supporting the creation of active learning in TK Lebijaga.